In situ analysis of a composting plant located in São Paulo city: fungal ecology in different composting phases (Acta Scientiarum. Biological Sciences, 2019)
The National Plan for Solid Waste has set out to reduce by 25% the amount of organic waste disposed of in landfills, mostly food residues from street fairs, besides determining the implementation of municipal composting plants, and it also mentions improving the capacity of plants already installed. The purpose of the study was to analyze which decomposing fungi are involved in the different composting phases, in a plant located in the city of São Paulo. Data was collected in four composting seasons from 2016 to 2017 and the analysis of 49 samples showed twelve genera belonging to the Ascomycetes and Zygomycetes phyla, but only at the mesophilic phase. In all seasons, yeasts and Aspergillus fumigatus were predominant with a total count of 1.0 x 109 cfu g-1 and 7.4 x 108 cfu g-1, respectively. These fungi can be applied in future studies of biostimulation to optimize the cycle at the municipal plant.